Analysis of Telebasis Selys, 1865—Part I. (Odonata: Coenagrionidae) - Lencioni, F.a.a. (Zootaxa, 2023)
All species of Telebasis Selys, 1865 are analyzed and Telebasis sensu lato is redefined, Helveciagrion Machado, 1980 is removed from synonym and revalidated based on morphological characters and a new genus (Juenagrion gen. nov.) and a new species (Juenagrion nanae spec. nov.—Brazil: Mato Grosso: Querência, córrego transição, 13° 03′ 35″ S & 52° 12′ 03″ W) are erected. Diagnostic illustrations are presented.